CONVEYING NATIONAL AND CULTURAL IDENTITY THROUGH THE TRANSLATION OF LITERARY WORKS - Selbi Batyrova (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This paper explores the representation of ethnocultural identity in Turkmen literature, focusing on the works of Berdi Kerbabaev, a prominent figure in Turkmen prose. Through a detailed analysis of Kerbabaev’s novel The Decisive Step, the study demonstrates how national character, family values, gender roles, and hospitality are intricately woven into narrative structures. By examining the author’s portrayal of Turkmen traditions, behaviors, and worldview, the paper highlights how literature becomes a means of preserving and transmitting cultural identity. The study also underscores the role of literary characters in embodying the collective consciousness of the Turkmen people, emphasizing the interaction between national values and universal human concepts. The research reveals that through the symbolic use of language, setting, and character development, Berdi Kerbabaev reflects the enduring ethical and spiritual values of the Turkmen nation.